2014
DOI: 10.1093/toxsci/kfu057
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Characterization of Serological, Pathological, and Functional Events in Doxorubicin-Induced Cardiotoxicity

Abstract: Many efficacious cancer treatments cause significant cardiac morbidity, yet biomarkers or functional indices of early damage, which would allow monitoring and intervention, are lacking. In this study, we have utilized a rat model of progressive doxorubicin (DOX)-induced cardiomyopathy, applying multiple approaches, including cardiac magnetic resonance imaging (MRI), to provide the most comprehensive characterization to date of the timecourse of serological, pathological, and functional events underlying this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 46 publications
4
36
0
1
Order By: Relevance
“…The present study showed decreased of physical activity; decline in general health, significantly lower body weight, and significant ascites in DOXadministered groups (II, III) at the end of the 3rd week. This is consistent with previous reports [Merlet et al, 2013;Cove-Smith et al, 2014;Ammar et al, 2015].…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed decreased of physical activity; decline in general health, significantly lower body weight, and significant ascites in DOXadministered groups (II, III) at the end of the 3rd week. This is consistent with previous reports [Merlet et al, 2013;Cove-Smith et al, 2014;Ammar et al, 2015].…”
Section: Discussionsupporting
confidence: 94%
“…The slight cTn rise observed in both groups might be at least partially explained by a cardiac burden induced by anesthesia, repeated blood sampling and animal manipulations, together with the excellent sensitivity of modern cardiac troponin immunoassays employed in this study. The lack of ANT-induced elevation of cTnT after the first dose is in an agreement with Cove-Smith et al [32] who reported that only electron microscopy of the myocardium revealed subcellular degeneration and marked mitochondrial changes after a single dose of doxorubicin, while Table 3 Correlation of area under curve (AUC) of cardiac troponins in 1st, 5th and 8th weeks and AUC 5-10 (calculated from the 5th till the 10th week) with left ventricular systolic function (LV fractional shortening and dP/dt max ). significant increases in serological cTnI (measured using a human ultrasensitive troponin I assay kit, Siemens, Camberley, UK) emerged later.…”
Section: Discussionsupporting
confidence: 91%
“…provided the most comprehensive characterization to the time course of events underlying chemotherapy‐related cardiomyopathy: while subcellular degeneration occurs after a single dose and progressive cardiomyocyte degeneration begins after two doses, extensive replacement fibrosis may develop during the off‐dosing period (functional indices assessed by cardiac MRI decline progressively and reach statistical significance after two doses), culminating in ‘clinical’ LV dysfunction by 12 weeks. Significant increases in peak myocardial contrast enhancement and serological cardiac troponin I have been shown to appear after eight doses, importantly preceding LVEF decline to <50% . Another aspect that may be evaluated is increased signal intensity on T1 and T2 weighted images and signal prolongation (in msec) on T1 and T2 maps due to myocyte loss and interstitial oedema.…”
Section: Diagnostic Toolsmentioning
confidence: 99%